A study on the interaction of N–acetylneyramic acid with monosaccharides adsorpbted on ultrafine silica surface - L. M. Ushakova; E. M. Demianenko; M. I. Terets; V. V. Lobanov; N. T. Kartel (Хімія, фізика та технологія поверхні, 2020)
Nowadays, it is relevant to study the processes that occur at the boundary of biomolecule (cell)-nanoparticle phase distribution. There is a growing interest in studying the interaction of ultrafine silica (UFC) with saccharides, in particular glucose and fructose, as well as with N-acetylneuraminic acid (NANA) (which is а part of the body’s cell membrane), for further creation of nanocomposites with biomolecules to use in biological systems. Using the density functional theory method (DFT) within the polarization continuum model (PCM), the interaction peculiarities of monosaccharides with silica surface were examined and the influence of the NANA molecule on this process was determined. The results of the analysis of quantum chemical calculations indicate that glucose and fructose can be used as modifiers for NANA adsorption. The molecules of these carbohydrates are related to silica surface and form a complex with N-acetylneuraminic acid. It is found that hydrogen bonds between hydroxyl groups of carbohydrates and silanol groups of the UFC surface play a major part in the formation of intermolecular complexes. The calculations show that the adsorption of monosaccharides on silica surface is possible considering their location, and it also depends on how to carry out the adsorption. That is, whether the adsorption of saccharides and then of NANA, or the adsorption from monosaccharides-NANA solution on silica surface is sequential.